ANALYSIS OF CALCIUM (Ca) CONTENT IN GUPPY FISH (Poecilia reticulata) AT KALIRUNGKUT WITH ICPS - Yellen Audina Wijaya; Kusuma Hendrajaya (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2021)
The aim of this study was to observe the calcium level in guppy fish from the ditch in Kalirungkut Village, Surabaya that potentially to be used as the source of raw material of animal feed in the form of fish flour. The destruction method used a wet destruction by using HNO3 and HCl. To analize qualtitatively and quantitatively of calcium used an ICPS instrument. By qualitative analysis, the peak was shown at wavelength 393,366 nm, proving the existence of calcium in a fish sample. And by quantitative analysis, guppy fish contains calcium with an average level of 4.28%. This indicates that guppy fish potentially to be used as a source of raw material for animal feed which is seen from the calcium levels having requirement of 2.5-5% calcium content